British construction industry: a landmark of environmentally sustainable practices to the world. (24th October 2022) - Maqbool, Rashid; Kandukuri, Vishal; Rashid, Yahya; Ashfaq, Saleha
This research provided the understanding of sustainability impacts caused by construction industry and how these can enhance the ecological aspect. Moreover, this research also investigated the hurdles which come in the way of sustainability and drivers for sustainable development in construction industry. The case of BedZED is critically evaluated in this research to understand and pose research dimensions. Mix-method techniques were adopted to collect 144 quantitative questionnaire surveys and five qualitative interview responses from the professionals working in UK construction industry. It was observed that 'compliance with the environment' received the highest rating by survey respondents, whereas 'capital cost' was not considered an important factor for the sustainable construction industry practices in the UK. The findings were also confirmed by five industrial experts through interviews, who believe if there is willingness to 'compliance with the environment' there is not much hindrance impact of 'capital cost' for sustained construction industry.